Gastroprotective Effect of Sinapic Acid on Ethanol-Induced Gastric Ulcers in Rats: Involvement of Nrf2/HO-1 and NF-κB Signaling and Antiapoptotic Role - Raish, Mohammad; Shahid, Mudassar; Bin Jardan, Yousef A.; Ansari, Mushtaq Ahmad; Alkharfy, Khalid M.; Ahad, Abdul; Abdelrahman, Ibrahim Abdelsalam; Ahmad, Ajaz; Al-Jenoobi, Fahad I. (Frontiers in Pharmacology, 2021)
Background: In the current study, we evaluated the therapeutic potential of sinapic acid (SA) in terms of the mechanism underlying its gastroprotective action against ethanol-induced gastric ulcers in rats. Methods: These effects were examined through gross macroscopic evaluation of the stomach cavity (gastric ulcer index [GUI]), alteration in pH, gastric juice volume, free acidity, total acidity, total gastric wall mucus, and changes in PGE2. In addition, we evaluated lipid peroxidation (malondialdehyde), antioxidant systems (catalase and glutathione), inflammatory markers (tumor necrosis factor-α [TNF-α] and interleukin-6 [IL-6], and myeloperoxidase [MPO]), apoptotic markers (caspase-3, Bax, and Bcl-2), nuclear factor-κB (NF-κB [p65]), NO levels, and histopathological staining (H&E and PAS). Results: In rats with ethanol-induced ulcers, pre-treatment with SA (40 mg/kg p.o.) decreased the sternness of ethanol-induced gastric mucosal injuries by decreasing the GUI, gastric juice volume, free acidity, and total acidity. In addition, the pH and total gastric mucosa were increased, together with histopathological alteration, neutrophil incursion, and increases in PGE2 and NO2. These effects were similar to those observed for omeprazole, a standard anti-ulcer drug. SA was shown to suppress gastric inflammation through decreasing TNF-α, IL-6, and MPO, as well as curbing gastric oxidative stress through the inhibition of lipid peroxidation (MDA) and restoration of depleted glutathione and catalase activity. SA inhibited Bcl-2-associated X (Bax) and caspase-3 activity, and restored the antiapoptotic protein Bcl-2; these findings indicate the antiapoptotic potential of SA, leading to enhanced cell survival. SA also repressed NF-κB signaling and increased IκBα. Moreover, SA upregulated the nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1), thereby restoring depleted antioxidant defense enzymes and implicating the NRF2/HO-1 signaling pathways. Conclusion: These results suggest that the prophylactic administration of SA (40 mg/kg) can ameliorate ethanol-induced gastric ulcers in rats primarily via the modulation of Nrf2/HO-1 and NF-κB signaling and subsequent enhancement of cell viability.